Simultaneous Determination of Two Coefficients of a Parabolic Equation in the Case of Nonlocal and Integral Conditions - Ivanov, M. I.; Pabyrivs’ka, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish conditions for the existence and uniqueness of a solution of the inverse problem for a parabolic equation with two unknown time-dependent coefficients in the case of nonlocal boundary conditions and integral overdetermination conditions.